Towards devising an efficient VQA in the Bengali Language - Islam, S M Shahriar; Auntor, Riyad Ahsan; Islam, Minhajul; Chowdhury, Tahmin Haider; Hossain Anik, Mohammad Yousuf (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2021.